Assessment of Carbon Dioxide Piscicide Treatments. (19th October 2018) - Cupp, Aaron R.; Smerud, Justin R.; Tix, John A.; Rivera, Jose M.; Kageyama, Stacie A.; Merkes, Christopher M.; Erickson, Richard A.; Amberg, Jon J.; Gaikowski, Mark P.
Abstract: Few chemicals are approved to control or eradicate nuisance fish populations in the United States. Carbon dioxide (CO2 ) is currently being developed and studied as a new piscicide option for nonselective population control. This study evaluated dry ice (solid state CO2 ) as a simple CO2 delivery method during winter piscicide applications. Nonnative Silver Carp Hypophthalmichthys molitrix, Bighead Carp H. nobilis, and native Fathead Minnow Pimephales promelas were overwintered together in ice‐covered ponds treated with 25 kg dry ice/100, 000 L (low treatment) or 50 kg dry ice/100, 000 L (high treatment). Overwinter fish survival was significantly reduced in ponds treated with dry ice relative to untreated control ponds. Fathead Minnows were less susceptible to CO2 exposure than the carps, with 26–96% survival in low‐treatment ponds and 4–68% survival in high‐treatment ponds. Silver Carp and Bighead Carp were more sensitive to CO2 treatments and no individuals of either species survived in ponds with the high‐treatment level. Water samples were also collected in all ponds throughout this study, and we observed notably higher Silver Carp and Bighead Carp environmental DNA (eDNA) concentrations in dry‐ice‐treated ponds relative to untreated control ponds. Distinct changes in eDNA trends correlated with fish mortality, and results indicate that eDNA sampling could be a useful indicator of piscicide efficacy. This study demonstrates that CO2 administered as dry ice is an effective under‐ice piscicide method.